2022
DOI: 10.1021/acsaelm.2c01164
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Solar-Blind UV Detectors Based on O-Terminated Vertical Diamond Schottky Diode with Low Dark Current, High Detectivity, and High Signal-to-Noise Ratio

Abstract: Self-powered solar-blind UV detectors were fabricated using high-quality Ru/diamond Schottky diodes. Photocurrents of 1 nA and 1.3 nA were obtained for detector Semi and Mesh under the condition of zero bias and 220 nm UV light irradiation, while the dark currents of these two detectors were 0.53 pA and 0.007 pA at 0 V, respectively. Photosensitive areas of detector Semi and Mesh were 1 mm 2 and 0.74 mm 2 , respectively. Rectification ratios as high as 1.5 × 10 7 and 5.7 × 10 8 at ±5 V for Semi and Mesh were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Many materials, such as Ag, Al, Au, Ru, WC etc., have been utilized to construct Schottky photodiodes . In 1996, Whitfield et al reported planar diamond photodiodes with gold Schottky and Ti/Ag/Au ohmic contacts shows a sharp cutoff in photoresponse in DUV with low dark currents under reverse biases. , To realize thermally stable Schottky contacts with diamond, Koide compared the rectifying characteristics of the metal contacts, such as Ti, Mo, Cr, Pd, Co, WC, and hafnium nitride (HfN), revealing that the Schottky electrode materials should not react with diamond at elevated temperatures. , The resulting photodetectors exhibit a high DUV/visible rejection ratio of 10 6 at a reverse bias of 2 V. In addition, the diamond-based photodiode using WC Schottky contact can operate in self-powered mode, achieving a DUV (210 nm)/visible rejection ratio of 10 5 at zero bias .…”
Section: Diamond-based Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many materials, such as Ag, Al, Au, Ru, WC etc., have been utilized to construct Schottky photodiodes . In 1996, Whitfield et al reported planar diamond photodiodes with gold Schottky and Ti/Ag/Au ohmic contacts shows a sharp cutoff in photoresponse in DUV with low dark currents under reverse biases. , To realize thermally stable Schottky contacts with diamond, Koide compared the rectifying characteristics of the metal contacts, such as Ti, Mo, Cr, Pd, Co, WC, and hafnium nitride (HfN), revealing that the Schottky electrode materials should not react with diamond at elevated temperatures. , The resulting photodetectors exhibit a high DUV/visible rejection ratio of 10 6 at a reverse bias of 2 V. In addition, the diamond-based photodiode using WC Schottky contact can operate in self-powered mode, achieving a DUV (210 nm)/visible rejection ratio of 10 5 at zero bias .…”
Section: Diamond-based Photodetectorsmentioning
confidence: 99%
“…Many materials, such as Ag, Al, Au, Ru, WC etc., have been utilized to construct Schottky photodiodes. 33 In 1996, Whitfield et al reported planar diamond photodiodes with gold Schottky and Ti/Ag/Au ohmic contacts shows a sharp cutoff in photoresponse in DUV with low dark currents under reverse biases. 33a , 33b To realize thermally stable Schottky contacts with diamond, Koide compared the rectifying characteristics of the metal contacts, such as Ti, Mo, Cr, Pd, Co, WC, and hafnium nitride (HfN), revealing that the Schottky electrode materials should not react with diamond at elevated temperatures.…”
Section: Diamond-based Photodetectorsmentioning
confidence: 99%
“…The peak responsivity of the photodetector was 21.8 A W −1 , and the detectivity was 1.39 × 10 12 cm Hz 1/2 W −1 when the bias voltage was 50 V (Figure 22b,c). Liu et al fabricated self-powered DUV detectors using high-quality Ru/diamond Schottky diodes [170]. Oxygen-terminated diamond was used because of its stable property and surface band bending.…”
Section: Peer Review 30 Of 41mentioning
confidence: 99%
“…(e) Dark current and (f) photocurrent (220 nm) vs. voltage for planar and groove-shaped electrode structures [160].The diamond-based Schottky photodiode is one of the most studied device geometries for solar-blind DUV photodetection. The effects of the photocurrent gain mechanism of Schottky devices and the trap state color center on the response have been studied[163][164][165][166][167][168][169][170].…”
mentioning
confidence: 99%
“…Ultraviolet (UV) photodetectors, which can convert light into electrical signals, play a crucial role in aerospace detection, missile tracking, optical communications, and fire warning. [1][2][3] The third-generated wide bandgap semiconductors represented by ZnO, [4][5][6] GaN, [7,8] SiC, [9,10] Ga 2 O 3 , [11,12] and diamond, [13] which are promising choices for constructing the heterojunction UV photodetector owing to their suitable cut-off wavelength determined by their bandgap, high chemical stability, good thermal conductivity and high saturation electron drift speed. [14][15][16] Whereas the intrinsic limits of imperfect interfacial transportation impede the further improvement of highperformance photodetector.…”
Section: Introductionmentioning
confidence: 99%